Stability Analysis of Type-2 Fuzzy Process Control Using LMI - Rajendran, Manivasagam; Aruchunan, Prabhu (Review of Computer Engineering Research, 2019)
This paper exhibits a type of fuzzy robust plan designed for nonlinear time-delay system based on the fuzzy Lyapunov method. In addition, the obtainable delay-self-governing state is changed into linear matrix inequalities (LMIs) consequently the fuzzy state response gain and regular solutions are numerically possible by nature inspired optimization algorithm. LMI approach for determining robust stability of non-linear system such as to an exothermic continuous-time stirred tank reactor (CSTR) by parametric uncertainties. Essential and satisfactory circumstances intended for stabilization of a linear continuous-time uncertain system through static output feedback are specified at earliest. After that the difficulty of robust static output feedback control plan is transformed to resolution of linear matrix inequalities (LMIs) and two LMI based algorithms, iterative and non-iterative ones are used. The design process guarantee by satisfactory circumstances the healthy quadratic stability and assured price. The opportunity to utilize a healthy static output response for control of CSTRs with suspicions is verified via simulation results.